PROGRAM PELATIHAN KEAGAMAAN DALAM MEMBINA MORAL REMAJA DI DESA BIANGLOE KECAMATAN PA’JUKUKANG KABUPATEN BANTAENG - Syam, Mutmainnah; Latif, M. Ali; B, Muhaemin (JAPPA: Jurnal Andragogi Pedagogi dan Pemberdayaan Masyarakat, 2023)
This research examines the Religious Training Program in Fostering Youth Morale in Biangloe Village, Pa'jukukang District, Bantaeng Regency. The purpose of the research is to find out the training model used, what obstacles are experienced and what efforts are made to overcome the existing obstacles. Using a qualitative approach to the type of case study research using descriptive methods. The research subjects were mosque youth caretakers and supervisors. Collecting data using interviews, observation, and documentation. The techniques used in data analysis are data reduction, data exposure, and inference. Triangulation is used to explain the validity of the data using various sources and techniques. The results of the study showed: 1) the religious training program carried out by youth in the mosque was preacher training using a three-step training model, namely first analyzing the problem, formulating and improving the training objectives. The second is sorting learning media and training methods. Third, consider the results of the exercise. 2) Obstacles in fostering youth at the Ma'lero Mosque come from internal factors and external factors 3) Efforts to overcome these obstacles, both from internal strengthening and external factors